2016
DOI: 10.4103/1450-1147.165353
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic neuroendocrine tumor with extensive bone marrow involvement at diagnosis: Evaluation of response and hematological toxicity profile of PRRT with 177Lu-DOTATATE

Abstract: The aim of this study was to evaluate the response and hematological toxicity in peptide receptor radionuclide therapy (PRRT) with lutetium (177Lu)-DOTA-octreotate (DOTATATE) in metastatic neuroendocrine tumor (NET) with extensive bone marrow metastasis at the initial diagnosis. A retrospective evaluation was undertaken for this purpose: Patients with NET with extensive diffuse bone marrow involvement at diagnosis who had received at least three cycles of PRRT with 177Lu-DOTATATE were considered for the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…In a meta-analysis comprising 16 studies, short-term myelotoxicity was observed in 10% (221/2104) with PRRT monotherapy. At the same time the grade 3/4 hematotoxicity was observed in 10.2% (7/68) of NET patients treated with 177 Lu (Sabet et al 2013b) having bone metastases and no hematotoxicity apart from grade 1 anemia in one out of six NET patients treated with 177 Lu (Basu et al 2016) having extensive bone marrow involvement shows that PRRT is well tolerated in this group of patients. Furthermore, MDS or AL were reported to range from 1.4% (3/208) with 177 Lu (Sabet et al 2013a); 2.0% (22/148) with 90 Y or 177 Lu (Baum et al 2018); 2.2% (13/582) with 177 Lu (Brabander et al 2017); and to 1.4% (32/2225) in the meta-analysis comprising 16 studies (Kesavan & Turner 2016).…”
Section: Toxicity Profiles Of Prrtmentioning
confidence: 69%
“…In a meta-analysis comprising 16 studies, short-term myelotoxicity was observed in 10% (221/2104) with PRRT monotherapy. At the same time the grade 3/4 hematotoxicity was observed in 10.2% (7/68) of NET patients treated with 177 Lu (Sabet et al 2013b) having bone metastases and no hematotoxicity apart from grade 1 anemia in one out of six NET patients treated with 177 Lu (Basu et al 2016) having extensive bone marrow involvement shows that PRRT is well tolerated in this group of patients. Furthermore, MDS or AL were reported to range from 1.4% (3/208) with 177 Lu (Sabet et al 2013a); 2.0% (22/148) with 90 Y or 177 Lu (Baum et al 2018); 2.2% (13/582) with 177 Lu (Brabander et al 2017); and to 1.4% (32/2225) in the meta-analysis comprising 16 studies (Kesavan & Turner 2016).…”
Section: Toxicity Profiles Of Prrtmentioning
confidence: 69%
“…In patient B, prior radiotherapy could also be one of the reasons of rapid progression which has been associated with myelotoxicity apart from age > 70 years, impaired renal function, baseline cytopenias, prior number of therapies, and prior chemotherapy (alkylating agents) [21]. In 2016, Basu et al performed a retrospective analysis on 5 neuroendocrine tumor patients with bone marrow involvement who underwent 177 Lu-DOTATATE therapy, which reported no hematological toxicity in any of their patients [33]. However, 18 F-FDG PET/ CT uptake in the bone marrow lesions was non-existent, barring just two patients who showed low-grade 18 F-FDG uptake [33].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Basu et al performed a retrospective analysis on 5 neuroendocrine tumor patients with bone marrow involvement who underwent 177 Lu-DOTATATE therapy, which reported no hematological toxicity in any of their patients [33]. However, 18 F-FDG PET/ CT uptake in the bone marrow lesions was non-existent, barring just two patients who showed low-grade 18 F-FDG uptake [33]. In the two cases we present here, both patients had very high SUV max values of their bone marrow lesions prior to PRRT therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The standard guideline recommendation for PRRT includes well-differentiated Grade 1 and Grade 2 NETs that express SSTR positivity, as evaluated by SRI with 68 Ga-DOTA-TOC/TATE/NOC PET/CT or 99m Tc-HYNIC-TOC scintigraphy or 111 In-octreoscan. The recently published European Society for Medical Oncology Clinical Practice Guidelines (ESMO CPG) have recommended PRRT up to the upper limit of Ki-67 LI to 30% 28 . Haug et al 29 applied SUV T/S (SUV max of the tumor-to-spleen ratio) to evaluate the response to somatostatin receptor-mediated radionuclide therapy in patients with well-differentiated neuroendocrine tumors and proved ΔSUV T/S was superior to baseline SUV max and ΔSUV max for the prediction of treatment outcome.…”
Section: Discussionmentioning
confidence: 99%